Study of plasmid profile and susceptibility patterns of Escherichia coli isolated from patients with urinary tract infection in Basra - Al-Hamdani , Maithem (University of Thi-Qar Journal of Science, 2013)
The present study was designed to investigate plasmid profiles and the prevalence of multidrug resistant Escherichia coli, which was done in Basra, Iraq, during the period between September 2012 and January 2013. A total of 306 urine sample were collected and cultured from patients with UTI , only 137 sample give positive growth.72 isolates diagnosed as E.coli isolates and tested for antibiotic susceptibility ,high antibiotic resistance toAmpcillin100%,Cefazolin93.05%,Augmentin83.33%,and Nitrofurantion70.83%, mid resistance to Piperacillin62.5%, Cefixime63.88%, Kanamycin48.61%, Cefepime43.05%, , ceftriaxone40.27%, , and Tobramycin36.11%,low resistance to Cotrimoxazole25%, Ciprofloxacin23.6%, Nalidixic Acid23.6% ,Aztreonam18.05%, Norfloxacin15.27%,Amikacin9.72%,Gentamicin8.33%, Chloramphenicol5.55%, cefoxitin1.38%, and Imipenen 0% .E.coli isolates showed multiple antibiotic resistance .The MAR index of the isolated ranged between 0.2 and 0.8 . Most isolates harbor large molecular weight plasmids ranging from (1- >10) Kbp.